(* Title: HOL/Computational_Algebra/Fraction_Field.thy Author: Amine Chaieb, University of Cambridge *) section‹A formalization of the fraction field of any integral domain; generalization of theory Rat from int to any integral domain› theory Fraction_Field imports Main begin subsection ‹General fractions construction› subsubsection ‹Construction of the type of fractions› context idom begin definition fractrel :: "'a × 'a ⇒ 'a * 'a ⇒ bool" where "fractrel = (λx y. snd x ≠ 0 ∧ snd y ≠ 0 ∧ fst x * snd y = fst y * snd x)" lemma fractrel_iff [simp]: "fractrel x y ⟷ snd x ≠ 0 ∧ snd y ≠ 0 ∧ fst x * snd y = fst y * snd x" by (simp add: fractrel_def) lemma symp_fractrel: "symp fractrel" by (simp add: symp_def) lemma transp_fractrel: "transp fractrel" proof (rule transpI, unfold split_paired_all) fix a b a' b' a'' b'' :: 'a assume A: "fractrel (a, b) (a', b')" assume B: "fractrel (a', b') (a'', b'')" have "b' * (a * b'') = b'' * (a * b')" by (simp add: ac_simps) also from A have "a * b' = a' * b" by auto also have "b'' * (a' * b) = b * (a' * b'')" by (simp add: ac_simps) also from B have "a' * b'' = a'' * b'" by auto also have "b * (a'' * b') = b' * (a'' * b)" by (simp add: ac_simps) finally have "b' * (a * b'') = b' * (a'' * b)" . moreover from B have "b' ≠ 0" by auto ultimately have "a * b'' = a'' * b" by simp with A B show "fractrel (a, b) (a'', b'')" by auto qed lemma part_equivp_fractrel: "part_equivp fractrel" using _ symp_fractrel transp_fractrel by(rule part_equivpI)(rule exI[where x="(0, 1)"]; simp) end quotient_type (overloaded) 'a fract = "'a :: idom × 'a" / partial: "fractrel" by(rule part_equivp_fractrel) subsubsection ‹Representation and basic operations› lift_definition Fract :: "'a :: idom ⇒ 'a ⇒ 'a fract" is "λa b. if b = 0 then (0, 1) else (a, b)" by simp lemma Fract_cases [cases type: fract]: obtains (Fract) a b where "q = Fract a b" "b ≠ 0" by transfer simp lemma Fract_induct [case_names Fract, induct type: fract]: "(⋀a b. b ≠ 0 ⟹ P (Fract a b)) ⟹ P q" by (cases q) simp lemma eq_fract: shows "⋀a b c d. b ≠ 0 ⟹ d ≠ 0 ⟹ Fract a b = Fract c d ⟷ a * d = c * b" and "⋀a. Fract a 0 = Fract 0 1" and "⋀a c. Fract 0 a = Fract 0 c" by(transfer; simp)+ instantiation fract :: (idom) comm_ring_1 begin lift_definition zero_fract :: "'a fract" is "(0, 1)" by simp lemma Zero_fract_def: "0 = Fract 0 1" by transfer simp lift_definition one_fract :: "'a fract" is "(1, 1)" by simp lemma One_fract_def: "1 = Fract 1 1" by transfer simp lift_definition plus_fract :: "'a fract ⇒ 'a fract ⇒ 'a fract" is "λq r. (fst q * snd r + fst r * snd q, snd q * snd r)" by(auto simp add: algebra_simps) lemma add_fract [simp]: "⟦ b ≠ 0; d ≠ 0 ⟧ ⟹ Fract a b + Fract c d = Fract (a * d + c * b) (b * d)" by transfer simp lift_definition uminus_fract :: "'a fract ⇒ 'a fract" is "λx. (- fst x, snd x)" by simp lemma minus_fract [simp]: fixes a b :: "'a::idom" shows "- Fract a b = Fract (- a) b" by transfer simp lemma minus_fract_cancel [simp]: "Fract (- a) (- b) = Fract a b" by (cases "b = 0") (simp_all add: eq_fract) definition diff_fract_def: "q - r = q + - (r::'a fract)" lemma diff_fract [simp]: "⟦ b ≠ 0; d ≠ 0 ⟧ ⟹ Fract a b - Fract c d = Fract (a * d - c * b) (b * d)" by (simp add: diff_fract_def) lift_definition times_fract :: "'a fract ⇒ 'a fract ⇒ 'a fract" is "λq r. (fst q * fst r, snd q * snd r)" by(simp add: algebra_simps) lemma mult_fract [simp]: "Fract (a::'a::idom) b * Fract c d = Fract (a * c) (b * d)" by transfer simp lemma mult_fract_cancel: "c ≠ 0 ⟹ Fract (c * a) (c * b) = Fract a b" by transfer simp instance proof fix q r s :: "'a fract" show "(q * r) * s = q * (r * s)" by (cases q, cases r, cases s) (simp add: eq_fract algebra_simps) show "q * r = r * q" by (cases q, cases r) (simp add: eq_fract algebra_simps) show "1 * q = q" by (cases q) (simp add: One_fract_def eq_fract) show "(q + r) + s = q + (r + s)" by (cases q, cases r, cases s) (simp add: eq_fract algebra_simps) show "q + r = r + q" by (cases q, cases r) (simp add: eq_fract algebra_simps) show "0 + q = q" by (cases q) (simp add: Zero_fract_def eq_fract) show "- q + q = 0" by (cases q) (simp add: Zero_fract_def eq_fract) show "q - r = q + - r" by (cases q, cases r) (simp add: eq_fract) show "(q + r) * s = q * s + r * s" by (cases q, cases r, cases s) (simp add: eq_fract algebra_simps) show "(0::'a fract) ≠ 1" by (simp add: Zero_fract_def One_fract_def eq_fract) qed end lemma of_nat_fract: "of_nat k = Fract (of_nat k) 1" by (induct k) (simp_all add: Zero_fract_def One_fract_def) lemma Fract_of_nat_eq: "Fract (of_nat k) 1 = of_nat k" by (rule of_nat_fract [symmetric]) lemma fract_collapse: "Fract 0 k = 0" "Fract 1 1 = 1" "Fract k 0 = 0" by(transfer; simp)+ lemma fract_expand: "0 = Fract 0 1" "1 = Fract 1 1" by (simp_all add: fract_collapse) lemma Fract_cases_nonzero: obtains (Fract) a b where "q = Fract a b" and "b ≠ 0" and "a ≠ 0" | (0) "q = 0" proof (cases "q = 0") case True then show thesis using 0 by auto next case False then obtain a b where "q = Fract a b" and "b ≠ 0" by (cases q) auto with False have "0 ≠ Fract a b" by simp with ‹b ≠ 0› have "a ≠ 0" by (simp add: Zero_fract_def eq_fract) with Fract ‹q = Fract a b› ‹b ≠ 0› show thesis by auto qed subsubsection ‹The field of rational numbers› context idom begin subclass ring_no_zero_divisors .. end instantiation fract :: (idom) field begin lift_definition inverse_fract :: "'a fract ⇒ 'a fract" is "λx. if fst x = 0 then (0, 1) else (snd x, fst x)" by(auto simp add: algebra_simps) lemma inverse_fract [simp]: "inverse (Fract a b) = Fract (b::'a::idom) a" by transfer simp definition divide_fract_def: "q div r = q * inverse (r:: 'a fract)" lemma divide_fract [simp]: "Fract a b div Fract c d = Fract (a * d) (b * c)" by (simp add: divide_fract_def) instance proof fix q :: "'a fract" assume "q ≠ 0" then show "inverse q * q = 1" by (cases q rule: Fract_cases_nonzero) (simp_all add: fract_expand eq_fract mult.commute) next fix q r :: "'a fract" show "q div r = q * inverse r" by (simp add: divide_fract_def) next show "inverse 0 = (0:: 'a fract)" by (simp add: fract_expand) (simp add: fract_collapse) qed end subsubsection ‹The ordered field of fractions over an ordered idom› instantiation fract :: (linordered_idom) linorder begin lemma less_eq_fract_respect: fixes a b a' b' c d c' d' :: 'a assumes neq: "b ≠ 0" "b' ≠ 0" "d ≠ 0" "d' ≠ 0" assumes eq1: "a * b' = a' * b" assumes eq2: "c * d' = c' * d" shows "((a * d) * (b * d) ≤ (c * b) * (b * d)) ⟷ ((a' * d') * (b' * d') ≤ (c' * b') * (b' * d'))" proof - let ?le = "λa b c d. ((a * d) * (b * d) ≤ (c * b) * (b * d))" { fix a b c d x :: 'a assume x: "x ≠ 0" have "?le a b c d = ?le (a * x) (b * x) c d" proof - from x have "0 < x * x" by (auto simp add: zero_less_mult_iff) then have "?le a b c d = ((a * d) * (b * d) * (x * x) ≤ (c * b) * (b * d) * (x * x))" by (simp add: mult_le_cancel_right) also have "... = ?le (a * x) (b * x) c d" by (simp add: ac_simps) finally show ?thesis . qed } note le_factor = this let ?D = "b * d" and ?D' = "b' * d'" from neq have D: "?D ≠ 0" by simp from neq have "?D' ≠ 0" by simp then have "?le a b c d = ?le (a * ?D') (b * ?D') c d" by (rule le_factor) also have "... = ((a * b') * ?D * ?D' * d * d' ≤ (c * d') * ?D * ?D' * b * b')" by (simp add: ac_simps) also have "... = ((a' * b) * ?D * ?D' * d * d' ≤ (c' * d) * ?D * ?D' * b * b')" by (simp only: eq1 eq2) also have "... = ?le (a' * ?D) (b' * ?D) c' d'" by (simp add: ac_simps) also from D have "... = ?le a' b' c' d'" by (rule le_factor [symmetric]) finally show "?le a b c d = ?le a' b' c' d'" . qed lift_definition less_eq_fract :: "'a fract ⇒ 'a fract ⇒ bool" is "λq r. (fst q * snd r) * (snd q * snd r) ≤ (fst r * snd q) * (snd q * snd r)" by (clarsimp simp add: less_eq_fract_respect) definition less_fract_def: "z < (w::'a fract) ⟷ z ≤ w ∧ ¬ w ≤ z" lemma le_fract [simp]: "⟦ b ≠ 0; d ≠ 0 ⟧ ⟹ Fract a b ≤ Fract c d ⟷ (a * d) * (b * d) ≤ (c * b) * (b * d)" by transfer simp lemma less_fract [simp]: "⟦ b ≠ 0; d ≠ 0 ⟧ ⟹ Fract a b < Fract c d ⟷ (a * d) * (b * d) < (c * b) * (b * d)" by (simp add: less_fract_def less_le_not_le ac_simps) instance proof fix q r s :: "'a fract" assume "q ≤ r" and "r ≤ s" then show "q ≤ s" proof (induct q, induct r, induct s) fix a b c d e f :: 'a assume neq: "b ≠ 0" "d ≠ 0" "f ≠ 0" assume 1: "Fract a b ≤ Fract c d" assume 2: "Fract c d ≤ Fract e f" show "Fract a b ≤ Fract e f" proof - from neq obtain bb: "0 < b * b" and dd: "0 < d * d" and ff: "0 < f * f" by (auto simp add: zero_less_mult_iff linorder_neq_iff) have "(a * d) * (b * d) * (f * f) ≤ (c * b) * (b * d) * (f * f)" proof - from neq 1 have "(a * d) * (b * d) ≤ (c * b) * (b * d)" by simp with ff show ?thesis by (simp add: mult_le_cancel_right) qed also have "... = (c * f) * (d * f) * (b * b)" by (simp only: ac_simps) also have "... ≤ (e * d) * (d * f) * (b * b)" proof - from neq 2 have "(c * f) * (d * f) ≤ (e * d) * (d * f)" by simp with bb show ?thesis by (simp add: mult_le_cancel_right) qed finally have "(a * f) * (b * f) * (d * d) ≤ e * b * (b * f) * (d * d)" by (simp only: ac_simps) with dd have "(a * f) * (b * f) ≤ (e * b) * (b * f)" by (simp add: mult_le_cancel_right) with neq show ?thesis by simp qed qed next fix q r :: "'a fract" assume "q ≤ r" and "r ≤ q" then show "q = r" proof (induct q, induct r) fix a b c d :: 'a assume neq: "b ≠ 0" "d ≠ 0" assume 1: "Fract a b ≤ Fract c d" assume 2: "Fract c d ≤ Fract a b" show "Fract a b = Fract c d" proof - from neq 1 have "(a * d) * (b * d) ≤ (c * b) * (b * d)" by simp also have "... ≤ (a * d) * (b * d)" proof - from neq 2 have "(c * b) * (d * b) ≤ (a * d) * (d * b)" by simp then show ?thesis by (simp only: ac_simps) qed finally have "(a * d) * (b * d) = (c * b) * (b * d)" . moreover from neq have "b * d ≠ 0" by simp ultimately have "a * d = c * b" by simp with neq show ?thesis by (simp add: eq_fract) qed qed next fix q r :: "'a fract" show "q ≤ q" by (induct q) simp show "(q < r) = (q ≤ r ∧ ¬ r ≤ q)" by (simp only: less_fract_def) show "q ≤ r ∨ r ≤ q" by (induct q, induct r) (simp add: mult.commute, rule linorder_linear) qed end instantiation fract :: (linordered_idom) linordered_field begin definition abs_fract_def2: "¦q¦ = (if q < 0 then -q else (q::'a fract))" definition sgn_fract_def: "sgn (q::'a fract) = (if q = 0 then 0 else if 0 < q then 1 else - 1)" theorem abs_fract [simp]: "¦Fract a b¦ = Fract ¦a¦ ¦b¦" unfolding abs_fract_def2 not_le [symmetric] by transfer (auto simp add: zero_less_mult_iff le_less) instance proof fix q r s :: "'a fract" assume "q ≤ r" then show "s + q ≤ s + r" proof (induct q, induct r, induct s) fix a b c d e f :: 'a assume neq: "b ≠ 0" "d ≠ 0" "f ≠ 0" assume le: "Fract a b ≤ Fract c d" show "Fract e f + Fract a b ≤ Fract e f + Fract c d" proof - let ?F = "f * f" from neq have F: "0 < ?F" by (auto simp add: zero_less_mult_iff) from neq le have "(a * d) * (b * d) ≤ (c * b) * (b * d)" by simp with F have "(a * d) * (b * d) * ?F * ?F ≤ (c * b) * (b * d) * ?F * ?F" by (simp add: mult_le_cancel_right) with neq show ?thesis by (simp add: field_simps) qed qed next fix q r s :: "'a fract" assume "q < r" and "0 < s" then show "s * q < s * r" proof (induct q, induct r, induct s) fix a b c d e f :: 'a assume neq: "b ≠ 0" "d ≠ 0" "f ≠ 0" assume le: "Fract a b < Fract c d" assume gt: "0 < Fract e f" show "Fract e f * Fract a b < Fract e f * Fract c d" proof - let ?E = "e * f" and ?F = "f * f" from neq gt have "0 < ?E" by (auto simp add: Zero_fract_def order_less_le eq_fract) moreover from neq have "0 < ?F" by (auto simp add: zero_less_mult_iff) moreover from neq le have "(a * d) * (b * d) < (c * b) * (b * d)" by simp ultimately have "(a * d) * (b * d) * ?E * ?F < (c * b) * (b * d) * ?E * ?F" by (simp add: mult_less_cancel_right) with neq show ?thesis by (simp add: ac_simps) qed qed qed (fact sgn_fract_def abs_fract_def2)+ end instantiation fract :: (linordered_idom) distrib_lattice begin definition inf_fract_def: "(inf :: 'a fract ⇒ 'a fract ⇒ 'a fract) = min" definition sup_fract_def: "(sup :: 'a fract ⇒ 'a fract ⇒ 'a fract) = max" instance by standard (simp_all add: inf_fract_def sup_fract_def max_min_distrib2) end lemma fract_induct_pos [case_names Fract]: fixes P :: "'a::linordered_idom fract ⇒ bool" assumes step: "⋀a b. 0 < b ⟹ P (Fract a b)" shows "P q" proof (cases q) case (Fract a b) { fix a b :: 'a assume b: "b < 0" have "P (Fract a b)" proof - from b have "0 < - b" by simp then have "P (Fract (- a) (- b))" by (rule step) then show "P (Fract a b)" by (simp add: order_less_imp_not_eq [OF b]) qed } with Fract show "P q" by (auto simp add: linorder_neq_iff step) qed lemma zero_less_Fract_iff: "0 < b ⟹ 0 < Fract a b ⟷ 0 < a" by (auto simp add: Zero_fract_def zero_less_mult_iff) lemma Fract_less_zero_iff: "0 < b ⟹ Fract a b < 0 ⟷ a < 0" by (auto simp add: Zero_fract_def mult_less_0_iff) lemma zero_le_Fract_iff: "0 < b ⟹ 0 ≤ Fract a b ⟷ 0 ≤ a" by (auto simp add: Zero_fract_def zero_le_mult_iff) lemma Fract_le_zero_iff: "0 < b ⟹ Fract a b ≤ 0 ⟷ a ≤ 0" by (auto simp add: Zero_fract_def mult_le_0_iff) lemma one_less_Fract_iff: "0 < b ⟹ 1 < Fract a b ⟷ b < a" by (auto simp add: One_fract_def mult_less_cancel_right_disj) lemma Fract_less_one_iff: "0 < b ⟹ Fract a b < 1 ⟷ a < b" by (auto simp add: One_fract_def mult_less_cancel_right_disj) lemma one_le_Fract_iff: "0 < b ⟹ 1 ≤ Fract a b ⟷ b ≤ a" by (auto simp add: One_fract_def mult_le_cancel_right) lemma Fract_le_one_iff: "0 < b ⟹ Fract a b ≤ 1 ⟷ a ≤ b" by (auto simp add: One_fract_def mult_le_cancel_right) end